Surgical treatment for primary pulmonary lymphoepithelioma-like carcinoma - Lin, Zhichao (Interact Cardiovasc Thorac Surg, 2016)
OBJECTIVES: Primary pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare but unique subtype of non-small-cell lung cancer (NSCLC). Our study aimed to evaluate clinicopathological characteristics and the value of surgical treatment for LELC and explore the relevant prognostic factors in a relatively large cohort. METHODS: We retrospectively reviewed the medical records of 39 lung LELC patients who underwent pulmonary resection with curative intent between January 2009 and December 2013. The clinical and pathological characteristics, survival data and relevant prognostic factors were analysed. RESULTS: The median age of lung LELC patients was 47 years (36–81), and 32 of 39 patients were non-smokers (82.1%). Positive expression of P63 and CK5/6 was shown in all the tested LELC specimens. In situ hybridization of Epstein–Bar virus-encoded RNA (EBER) was performed in 36 patients and all of them were positive. However, epidermal growth factor receptor (EGFR) mutational analysis was done in 19 patients and all of them were wild-type. The median follow-up time was 26.0 months in our cohort, and 6-, 12-, 24- and 36-month recurrence-free survival (RFS) rates were 92, 82, 73 and 73%, respectively. Patients with positive lymph nodes experienced significantly worse postoperative RFS than those with negative ones (P = 0.002). Multivariate survival analysis confirmed that only lymph node involvement [RR 0.051; 95% confidence interval, 0.003–0.991, P = 0.049] was an independent prognostic factor. CONCLUSIONS: Primary lung LELC is closely associated with Epstein–Bar virus infection but not involved in EGFR mutation pathway. Radical surgery could achieve a good outcome for resectable pulmonary LELC, and regional lymph node status is a vital prognostic factor.